Validation of Organizational Isomorphism Model Using Fuzzy Delphi Method - Najmeh Rezasoltani; Mehrdad Moharramzadeh; Nasrin Azizian Kohan; Abbas Naghizadeh-Baghi (Archives in Sport Management and Leadership)
The purpose of this research was to validate the organizational isomorphism model in sports federations using the Fuzzy Delphi Method. The method of this research was mixed and applied in terms of purpose, and the sampling method was theoretical. In the qualitative part, the process of data analysis continued until reaching theoretical saturation. The number of participants in the qualitative section was 12. The criteria for entering the research were to have at least two years of experience as a member of the board of directors of one of the sports federations. The research data collection tool was semi-structured interviews. The duration of each interview was between 15 and 75 minutes. Research validation was achieved through triangulation. Thematic analysis method was used to analyze the data. In the quantitative part, for the validation of the isomorphism model, a fuzzy Delphi group was formed with the presence of 12 sport managers and professors and elites in the field of sport management, all of whom had management experience in sports organizations. The research tool was the inventory of organizational isomorphism in sports federations, which was compiled based on the dimensions and indicators counted from the qualitative stage. The findings of the research showed that the isomorphism model of sports federations consisting of nine dimensions of pressures, interventionist factors, activist strategies, and consequences has sufficient and necessary validity. Therefore, managers of sports federations can rely on these findings to take steps to control and guide the phenomenon of isomorphism in their organization.